Fault Tolerance of Switch Blocks and Switch Block Arrays in FPGA. - Huang, J. (IEEE Transactions on VLSI systems)
A new application-independent approach for evaluating the fault tolerance of field-programmable gate-array (FPGA) interconnect structures is presented. Signal routing in the presence of faulty resources at switch block and FPGA levels is analyzed; this problem is directly related to the fault tolerance of FPGA interconnects for testing and reconfiguration at manufacturing and run-time applications. Two criteria are proposed and used as figure-of-merit for evaluating different FPGA interconnect architectures. The proposed approach is based on the number of available paths between pairs of end points and the probability to establish a one-to-one mapping between all input and output end points. A probabilistic approach is also presented to evaluate the fault-tolerant routing of the entire FPGA by connecting switch blocks in chains, as required for testing and to account for the input?output (I/O) pin restrictions of an FPGA chip. All possible interconnect faults for programmable switches and wiring channels are considered in the fault model. The proposed method is applicable to arbitrary switch block structures. Experimental results on commercial as well as academic designed FPGAs are presented and analyzed.